Analysis of Patient Satisfaction in the Registration Section at the Regional General Hospital in Mandau District, Bengkalis Regency in 2023 - Nasution, Gunung; Fahmi Oemar; Rinayanti Rasyad (Jurnal Manajemen dan Bisnis Terapan, 2023)
This study was conducted at the Mandau District General Hospital in Bengkalis Regency with the goal of determining patient satisfaction at the registration section in 2023 by looking at the level of satisfaction based on five quality dimensions, namely Reliability, Responsiveness, Assurance, Empathy, and Tangibles. A quantitative research design with a cross-sectional design was used in this investigation. This study's sample size was 300 persons. The Mann Whitney test was used to analyze data using univariate and bivariate analysis. According to the findings of the investigation, the overall level of patient satisfaction with the registration part was high for the majority of 184 people (61.3%). JKN patients have a modest level of satisfaction in the majority of quality characteristics. JKN patients reported moderate satisfaction on the reliability dimension, 52% on the responsiveness dimension, and 58.7% on the assurance dimension. Meanwhile, patients had high levels of satisfaction on the areas of empathy and tangibles, with 57.2% and 74.7%, respectively. Non-JKN patients had a high degree of satisfaction in all quality dimensions. 55.3% of Non-JKN patients reported high satisfaction on the reliability dimension, followed by 69.3% on the responsiveness dimension, 66.7% on the assurance dimension, 78% on the empathy dimension, and 80% on the tangibles component. There is a significant difference between the satisfaction of JKN and Non-JKN patients with the registration services at the Mandau District Hospital, Bengkalis Regency in 2023.